1995
DOI: 10.1159/000126837
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Secretion of Pro-Opiomelanocortin-Derived Peptides in Rats: Relative Importance of the Anterior and Intermediate Pituitary Lobes

Abstract: Stress stimulates secretion of the pro-opiomelanocortin (POMC)-derived peptides adrenocorticotropic hormone (ACTH), β-endorphin (β-END) and α-melanocyte-stimulating hormone (α-MSH) from the anterior lobe (AL) and intermediate lobe (IL) of the pituitary gland. The secretion of POMC-derived peptides from the AL and IL is differentially regulated and the relative contribution of the lobes may vary with the stimulus. We investigated (1) the relative importance of the AL and IL as source of POMC-derived peptides re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Recombinant Aβ 1–42 and Aβ 1–40 were purchased from Biopeptide Co. (San Diego, CA), and α-synuclein was expressed and purified as described (30). Aβ 1–40 and Aβ 1–42 were diluted in 0.5% Me 2 SO and 0.5 m Tris-HCl buffer (pH 7.4; 1 mg/ml) and then diluted into 40 μ m ThT solutions (in quadruplicate) containing or lacking the various forms of 7B2 in a total volume of 100 μl.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant Aβ 1–42 and Aβ 1–40 were purchased from Biopeptide Co. (San Diego, CA), and α-synuclein was expressed and purified as described (30). Aβ 1–40 and Aβ 1–42 were diluted in 0.5% Me 2 SO and 0.5 m Tris-HCl buffer (pH 7.4; 1 mg/ml) and then diluted into 40 μ m ThT solutions (in quadruplicate) containing or lacking the various forms of 7B2 in a total volume of 100 μl.…”
Section: Methodsmentioning
confidence: 99%
“…N-terminally acetylated -endorphin (NAc -end) and -melanocyte-stimulating hormone ( -MSH) are proopiomelanocortin (POMC)-derived peptide hormones produced and released by melanotrope cells in the pituitary pars intermedia. In many vertebrate classes, these hormones have been implicated in stress responses (Akil et al, 1985;Arends et al, 1999;Kjaer et al, 1995;Lindley et al, 1990;Lookingland et al, 1991;Mosconi et al, 1998;Wendelaar Bonga, 1997). In Mozambique tilapia (Oreochromis mossambicus), -MSH stimulates cortisol release from the interrenal cells in the head kidney (Lamers et al, 1992), and its corticotropic activity may be potentiated by NAc -end .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to GHR mRNA, Somatostatin (SS) and GH-releasing factor (GRF) neurons are also detected in the arcuate (ARC), periventricular (PeV) and paraventricular nuclei of the rat [4]. Several laboratories have reported that various kinds of stress decrease the circulating level of GH in the rat [5][6][7]. This repressive effect of stress on GH secretion is proposed to occur via stress-induced hypothalamic corticotropin-releasing factor (CRF) stimulating the inhibitory somatostatin release into portal blood [7].…”
mentioning
confidence: 99%